2016
DOI: 10.1038/srep21527
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Breakup in Expansion-contraction Microchannels

Abstract: We investigate the influences of expansion-contraction microchannels on droplet breakup in capillary microfluidic devices. With variations in channel dimension, local shear stresses at the injection nozzle and focusing orifice vary, significantly impacting flow behavior including droplet breakup locations and breakup modes. We observe transition of droplet breakup location from focusing orifice to injection nozzle, and three distinct types of recently-reported tip-multi-breaking modes. By balancing local shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 47 publications
(79 reference statements)
1
16
0
Order By: Relevance
“…Astonishingly, rear pinch-off inside the nozzle produces satellite drops with descending size distribution ( Fig. 5f ), which are similar to those generated by the tip-multi-breaking, a recently reported droplet breakup mode 44 45 . Despite their non-uniformity, the satellites depend on oscillation, which may provide an additional handle to harness the formation of droplets with various volumes, a required feature in some applications.…”
Section: Resultssupporting
confidence: 73%
“…Astonishingly, rear pinch-off inside the nozzle produces satellite drops with descending size distribution ( Fig. 5f ), which are similar to those generated by the tip-multi-breaking, a recently reported droplet breakup mode 44 45 . Despite their non-uniformity, the satellites depend on oscillation, which may provide an additional handle to harness the formation of droplets with various volumes, a required feature in some applications.…”
Section: Resultssupporting
confidence: 73%
“…Water droplets greater than 100 behave similar to a flat surface of liquid (Ho 1997), while droplets smaller than this size tend to behave as discontinuous phase. Recently, Zhu et al (2016) demonstrated how glycerol-water mixture breaks into smaller droplets as it moves through both expanding and contracting microcapillaries containing oil as the second phase (Figure 9). Creation of droplets in microcapillary has been covered extensively in a review by Baroud et al (2010).…”
Section: Evaporationmentioning
confidence: 99%
“…Figure 9: Influence of expanding-contracting microchannels on water droplet: a) schematic of microcapillary device (not on scale), b) droplets produced in sequence with decreasing size distribution 2, 4, 6, 8-drops, respectively. c) image of the expansioncontraction microchannel, and d) droplets produced with increasing orifice distance (from Zhu et al 2016).…”
Section: Evaporationmentioning
confidence: 99%
“…Until now, it offers the feasibility of handling miniature volumes, better mixing, encapsulation, sorting , and sensing—all of these are suitable for high‐throughput experiments . Despite its characteristic advantages in high‐throughput applications, benefits from the advantages of droplet‐based microfluidics requires a universal and comprehensive understanding of droplet generation to perform various logical operations such as sorting , merging , and breaking . This is one of the reasons it is a rapidly growing interdisciplinary field of research combining soft matter physics , biochemistry , and microsystems engineering .…”
Section: Introductionmentioning
confidence: 99%